Serious flaws in targeting LDL-C reduction in the management of cardiovascular disease in familial hypercholesterolemia. Issue 3 (4th March 2021) - Ravnskov, Uffe; de Lorgeril, Michel; Kendrick, Malcolm; Diamond, David M.
ABSTRACT: Recently, Polychronopoulos and Tziomalos reviewed research on the use of inclisiran and bempedoic acid in the management of cardiovascular disease (CVD) risk in people with familial hypercholesterolemia (FH). Their treatment recommendations were based on the general premise that high LDL-cholesterol (LDL-C) is inherently atherogenic, and that low levels of LDL-C need to be achieved to reduce CVD risk in FH individuals. However, their perspective on LDL-C is flawed at two levels of analysis: 1) They ignored the extensive literature demonstrating that CVD is not caused by high LDL-C; and 2) they failed to consider CVD treatment strategies that take into account the extensive literature that has shown that coagulation factors are more closely related to coronary events in FH than is LDL-C. In the following, we have briefly addressed each of these flaws in their review.